The Effect of Thyme and Nigella Oil on Some Properties of Acrylic Resin Denture Base - Nadira A Hatim; Amer A Taqa; Wafa Abbas; Arjwan M Shuker (University of Mosul, College of Dentistry, 2010)
Aims: To evaluating the preferable properties and concentrations of Genuine Nigella sativa and Thyme as oil low cost additive biocompatible antibiotic materials of denture base acrylic powder inre-lation to the commercially available heat cure acrylic resin material. Materials and Methods: One hundred and sixty acrylic resin Major heat cured samples were prepared without additives (Control), and with additives (A pure natural oil of Nigella sativa and Thyme 0.5%, 1%, 1.5%, and 2%) to eva-luate transverse strength, indentation hardness, color property, residual monomer, dimensional accura-cy, porosity, measurement of IR spectra, and anti-microbial-sensitivity tests. Results: Results showed a significant difference to P= 0.05. The addition of Thyme and Nigella oil increased the transverse strength, and hardness of the denture base materials, no porosities, an increase in residual monomer elution at 1st day, and both additives Nigella and Thyme oil act as antibacterial materials. Conclusions: The additives materials of pure natural oil of Nigella sativa and Thyme with concentration of 1.5% were recommended to give a proper properties, and as antimicrobial after curing of the acrylic resin denture base, but Thyme oil showed no effect on the color after curing in relation to Nigella sativa